Health Information Needs of Breast Cancer Survivors: An Umbrella Review - Nahid Gavili; Shahram Sedghi; Sirous Panahi; Maryam Razmgir (The Breast Journal)
Purpose. The aim of this umbrella review was to identify the main information needs of breast cancer survivors. Since several reviews have already been done on this topic, conducting an umbrella review not only combines their results but also gives a comprehensive picture and informative summary of breast cancer survivors’ needs. Method. The search was performed in PubMed, Embase, Scopus, Web of Science, ProQuest, Cochrane, and Google Scholar from inception to the end of March 2024. This review was conducted according to the JBI methodology for umbrella reviews, and the report was based on Rutten’s category for information needs of patients with cancer. After removing duplicate and irrelevant articles, 14 systematic reviews were included in the analysis. The JBI checklist was used for evaluating the quality of eligible articles. Results. The information needs were classified into 11 main categories and 86 subcategories. As a result of this umbrella review, one category was added to Rutten’s 10 categories. Also, treatment information needs were introduced as the main identified category. Information on supportive care needs ranked second, and body image/sexuality information needs ranked third with a slight difference. Conclusion. The information needs outlined in the present study can serve as a general model to help clinical decision makers and policymakers in order to better understand the needs of the group and meet the information needs of the population. Implications for Cancer Survivors. These recommendations can promote and develop targeted interventions to reduce the psychosocial consequences of breast cancer survivors and increase their quality of life.